100 Efficacy of vasopressin, steroid, and epinephrine protocol for in-hospital cardiac arrest resuscitation: a systematic review and meta-analysis of randomized controlled trials with trial sequential analysis. (6th June 2022) - Iltaf Satti, Danish; Lee, Yan Hiu Athena; Leung, Keith Sai Kit; Hui, Jeremy Man Ho; Kot, Thompson Ka Ming; Babar, Arslan; Mahalwar, Gauranga; Wai, Abraham KC; Liu, Tong; Roever, Leonardo; Tse, Gary; Chan, Jeffrey Shi Kai
Abstract : Objectives: To assess the effect of vasopressin, steroid and epinephrine (VSE) combination therapy on return of spontaneous circulation (ROSC) after in-hospital cardiac arrest (IHCA), and test the conclusiveness of evidence using trial sequential analysis (TSA). Methods: The systematic search included PubMed, EMBASE, Scopus, and Cochrane Central Register of Controlled Trials. Randomized controlled trials (RCTs) that included adult patients with IHCA, with at least one group receiving combined VSE therapy were selected. Data was extracted independently by two reviewers. The main outcome of interest was ROSC. Other outcomes included survival to hospital discharge or survival to 30 and 90 days, with good neurological outcomes. Results: We included a total of three RCTs (n=869 patients). Results showed that VSE combination therapy increased ROSC (risk ratio, 1.41; 95% CI, 1.25–1.59) as compared to placebo. TSA demonstrated that the existing evidence is conclusive. This was also validated by the alpha-spending adjusted relative risk (1.32 [1.16, 1.49], p<0.0001). Other outcomes could not be meta-analysed due to differences in timeframe in the included studies. Conclusion: VSE combination therapy administered in cardiopulmonary resuscitation led to improved rates of ROSC. Future trials of VSE therapy should evaluate survival to hospital discharge, neurological function and long-term survival. Conflict of Interest: None